The development and evaluation of a pilot school-based programme for prevention of HIV/AIDS among visually impaired and blind South African adolescents - Philander, J. H. (John Henry) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (DPhil)--University of Stellenbosch, 2007.